2019
DOI: 10.20884/1.agrin.2018.22.1.455
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMANASAN DAN ASAL EKSPLAN PADA PERTUMBUHAN DAN PERKEMBANGAN BAWANG MERAH (Allium ascolonicum L.)

Abstract: Tanaman bawang merah (Allium ascolonicum L) termasuk dalam genus Allium sp yang diperbanyak secaravegetatif melalui umbi. Perbanyakan benih bawang sudah dilakukan secara in vitro (konvensional), untuk tujuanpeningkatan mutu atau hanya perbanyakan tanaman . Penelitian dilaksanakan di Laboratorium Kultur JaringanBalai Penelitian Tanaman Sayuran, pada bulan Februari sampai Agustus 2014. Untuk menghasilkan tanamanbebas penyakit terutama virus dapat digunakan teknik kultur jaringan yang dikombinasikan dengan perlak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Explants in the form of shoot buds have the highest percentage of producing planlets, particularly when grown on auxin-free media [6]. The type of media used is B5 media, which has been used in a number of previous studies, including research conducted by Karjadi et al [7], which demonstrated that the best results for each change were obtained on B5 media with treatments such as, for the number of leaves at the NAA level of 0 mg/l with a BAP of 2.5 and 7.5 mg/l, and for plantlet height at NAA level 0 mg/l and BAP 2.5 mg/l, as well as for In light of this, it is crucial to conduct this research in order to obtain the optimal media by adding ZPT cytokinin in the form of BAP and kinetin to the zincon multiplication phase.…”
Section: Introductionmentioning
confidence: 99%
“…Explants in the form of shoot buds have the highest percentage of producing planlets, particularly when grown on auxin-free media [6]. The type of media used is B5 media, which has been used in a number of previous studies, including research conducted by Karjadi et al [7], which demonstrated that the best results for each change were obtained on B5 media with treatments such as, for the number of leaves at the NAA level of 0 mg/l with a BAP of 2.5 and 7.5 mg/l, and for plantlet height at NAA level 0 mg/l and BAP 2.5 mg/l, as well as for In light of this, it is crucial to conduct this research in order to obtain the optimal media by adding ZPT cytokinin in the form of BAP and kinetin to the zincon multiplication phase.…”
Section: Introductionmentioning
confidence: 99%